2002
DOI: 10.1124/mol.61.1.194
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Hepatocyte Nuclear Factor-4 to Down-Regulation of CYP2D6 Gene Expression by Nitric Oxide

Abstract: Nitric oxide (NO) released under inflammatory and infectious conditions has been implicated in the down-regulation of many cytochrome P450 genes, but its mechanism of action remains unknown. We showed that the expression of the CYP2D6 gene is down-regulated at the transcriptional level by NO in HepG2 cells. The NO donor (Ϯ)-N-[(E)-4-ethyl-2-[(Z)-hydroxyimino]-5-nitro-3-hexene-1-yl]-3-pyridine carboxamide (NOR4) decreased the expression of CYP2D6 mRNA in a concentrationdependent manner. Using a CYP2D6 promoter-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 34 publications
0
30
0
1
Order By: Relevance
“…7). The expression levels of several types of P450s in HepG2 cells have been reported to be lower than those in primary human hepatocytes (Jover et al, 1998;Hara and Adachi, 2002;Westerink and Schoonen, 2007). However, considerable metabolic activity of CYP2D6 was detected in HepG2 cells, and the drug-metabolizing activity also varied in a circadian fashion.…”
Section: Discussionmentioning
confidence: 97%
“…7). The expression levels of several types of P450s in HepG2 cells have been reported to be lower than those in primary human hepatocytes (Jover et al, 1998;Hara and Adachi, 2002;Westerink and Schoonen, 2007). However, considerable metabolic activity of CYP2D6 was detected in HepG2 cells, and the drug-metabolizing activity also varied in a circadian fashion.…”
Section: Discussionmentioning
confidence: 97%
“…It is well established that both of these enzymes exert negative regulatory control on several P450s (Hara and Adachi, 2002). Possible contributions of eNOS and iNOS to the down-regulation of CYP3A, CYP2C, and CYP2D cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…NO donors can down-regulate CYP mRNAs and proteins in colon carcinoma [25,26] and hepatocarcinoma [27] cell lines, and it was reported that in HT-29 cells, NOS2 inhibitors or antisense oligonucleotides could block the down-regulation of CYP3A4 protein by ceramide [28], a putative mediator of the effects of pro-inflammatory cytokines on CYP expression [29]. We are aware of one published study on the regulation of CYP expression by physiological or pharmacological NO in primary human hepatocytes, which is the optimal system to study regulation of the human drug-metabolizing CYPs.…”
Section: Introductionmentioning
confidence: 99%